0269 An International Historical Cohort Study of Workers in the Hard-Metal Industry: Mid-Study Epidemiology Update. (23rd June 2014) - Marsh, Gary; Buchanich, Jeanine; Zimmerman, Sarah; Kennedy, Kathleen; Esmen, Nurtan; Moshammer, Hanns; Morfeld, Peter; Erren, Thomas; Svartengren, Magnus; Westberg, Hakan; McElvenny, Damien; Cherrie, John
Abstract : Objectives: A multinational occupational epidemiological study of workers exposed to tungsten carbide with a cobalt binder (WCCo) is underway in the US and Europe. The epidemiological component will investigate total and cause-specific mortality risks and exposure-response relationships with focus on lung cancer. We designed the study to overcome certain limitations of earlier epidemiology studies. Method: The epidemiological and exposure assessment components of the study are coordinated by the University of Pittsburgh and the University of Illinois at Chicago, respectively. Our cohort comprises 12 manufacturing sites in the US and nine sites in Europe, and represents three companies, five countries (US, Austria, Germany, Sweden and UK) and multiple manufacturing processes and exposures. Statistical analyses will adjust external and internal mortality rate comparisons for potential co-exposures, including smoking histories obtained via a nested case-control study. The study will include separate and pooled analyses. Results: Our data collection effort identified two additional US study sites and additional subjects in the German and Swedish sites. Accordingly, our originally projected cohort size of 21 000 subjects has increased to 35 508 (US-7005; Europe-33 508). Vital status tracing, cause of death determination and identification of subjects for the nested case-control study are ongoing. Conclusions: Our study will enable country-specific and pooled analyses of mortality rates and exposure-response relationships among workers from 21 study sites and the opportunity to compare and contrast findings across countries, sites, companies and/or manufacturing processes and exposures involved in this global industry. We will detail progress to date on the US and combined epidemiological component of the study.